Uncovering patterns of cattle intensification across South America’s dry diagonal - Tobias Kuemmerle; Pedro D Fernández; Matthias Baumann; Jamie Burton (Environmental Research Letters)
Where cattle production expands into natural ecosystems, it typically leads to stark social–ecological impacts, including greenhouse gas emissions, biodiversity losses, and ecosystem degradation. This is particularly the case in South America’s tropical forests and savannas, where much hope is placed in intensifying cattle production instead of further expanding it. Yet, where such an intensification is already happening and how it is associated with deforestation patterns remains elusive. Here, we pioneer the use of satellite imagery to identify areas where cattle are confined—a key indicator of intensified cattle production—across the entire 3.7 million km ^2 South American dry diagonal; a global hotspot of cattle production and deforestation. We subsequently use an active-learning approach to separate these confinement areas into (1) feedlots, (2) concentrated animal feeding operations, and (3) supplementary feeding areas. Our results show that confinement areas are ubiquitous in the dry diagonal. We identified 253 large, industrialized feedlots and more than 3200 medium-sized concentrated animal feeding operations—together containing an estimated 13 million cattle head—and more than 4000 supplementary feeding sites on pastures. Feedlots were found mostly in the Cerrado ( n = 141), followed by Chaco ( n = 93), and were less frequent in the Chiquitano and Caatinga regions. Feedlots occurred predominantly in areas of high cropland cover and low levels of deforestation, while supplementary feeding sites were associated with higher shares of deforestation. Independent validation suggests our methodology can identify confinement areas robustly (97% user’s accuracy) and separate feedlots, concentrated animal feeding operations, and supplementary feeding sites accurately ( F 1-score 0.91 ± 0.01). Thus, our scalable approach has the potential to provide an advancement in our understanding of the distribution of cattle production systems, the geography of ranching intensification, the environmental impacts of beef production, and the relationship between ranching intensification and tropical deforestation.